Influences of Irreversibility in Transport of Peristaltic of Hybrid Nanomaterial through a Porous Medium in an Inclined Channel - Salih, Alaa Waleed; Abdulhadi, Ahmed M. (Iraqi Journal of Science, 2024)
The purpose of this work is to determine transferred heat features and irreversible transport peristaltic of nanomaterial fluid through a porous medium with an inclined symmetric channel. Expression of the basic velocity, pressure gradient, temperature, and stream function profiles within the boundary layer are plotted and discussed in detail via various values of the distinct parameters. Nanoparticles of hybrid nanomaterial impacts are also used. In the present article, water is used as a base liquid while nanoparticle contain polystyrene and graphene oxide. Over time, it is observed that there are distinct factors and effects such as magnetic field and porosity parameters. Mathematica software is used for estimating the exact solutions of axial velocity and temperature profiles. Additionally, the resolution of equations are considered under the small Reynolds number and  large wavelength approximation. Results with plotting graph access via MATHEMATICA (11) are listed.